Exploring Global Englishes content and language variation in an academic writing course. Issue 1 (21st April 2020) - Tardy, Christine M.; Reed, Kara; Slinkard, Jennifer R.; LaMance, Rachel
Abstract : The Global English language teaching (GELT) paradigm gives increased recognition to the plurality of varieties, users, and uses of English worldwide. However, application of GELT to the academic writing classroom can be challenging because of written language's reliance on codified standards; as such, few examples of GELT‐informed academic writing courses for English as an additional language (EAL) students are available to practitioners. In this article, the authors describe their institution's approach to designing a university academic writing course for EAL students that blends content‐based instruction and a language and genre awareness approach, critically engaging students with principles of Global Englishes. The course aims to provide support for academic language and writing development while embracing language difference as a norm. This article describes the course approach, design, and feedback while discussing challenges and benefits for EAL writing teachers and students.